Ação escolar junto aos alunos com necessidades educacionais especiais em situação de inclusão - Freitas, Cristiane Spada (2007)
With the aim of analyzing the school actions which have been developed with students who own special educational needs as far as inclusion is concerned, a bibliographic and documentary analyses and research has been made, followed by qualified branch and ethnographic related research. All the acquired data has been raised through surveys which have been developed in five public schools in the city of Mairiporã, situated in the Great Metropolitan area of São Paulo, with the support of the Governor s Education Bureau. It has also been shown and discussed taking into consideration the infra-structure features and the types of access conditions these students have. In addition, there have been interviews with each school principals and primary regular school teachers so as to find out criteria to distinguish and identify these special types of students in order to describe the elements which may make this inclusion process in the public city schools easy or hard. The interest for this branch has been grounded on the need of checking the ethic principles of equality and justice which must be guaranteed. Although there has been development, the present study has indicated a huge gap between the speech and the steps which have been taken, and that s why this process values must be checked, as something historic which has already begun and will certainly not end up soon. So, it must be deeply thought and understood within a dynamic focus. The results which have been found out might provide outstanding assistance for possible and necessary changes so as to lead to steps which shall be taken in the above-mentioned city schools.